Lionel Wendt : art and life - Baṇḍāra, Sampat; Fernando, Vijita (Nugegoda, Sri Lanka : Sarasavi Publishers, 2017)
Photographic tribute to Lionel Wendt, 1900-1944, Sri Lankan photographer and his associates.
Includes bibliographical references (page 129).
Keywords: Wendt, Lionel, -- 1900-1944.; Wendt, Lionel, -- 1900-1944 -- Friends and associates; Photographers -- Sri Lanka -- Biography; Sri Lanka -- Pictorial works; Sri Lanka -- Biography